Investigating Nutritional Value of Bassia scoparia Seed in vitro for Ruminants Nutrition in Arid and Semi-Arid Regions - Mohsen Sari; Yaser Monjezi; Jafar Nabati (پژوهشهای علوم دامی ایران, 2022)
Introduction: Halophytes are plants with ability to survive in saline and alkaline soils and are drought resistant. In many areas of the world, native and introduced halophytes are forage resources, especially for sustaining grazing livestock when other feeds are scarce. Iran is a typical country of wide deserts and saline ecosystems and halophytes plays a major role in the halophytic and xerophytic vegetation of Iran. kochia is a drought-resistant annual plant that its cultivation is increasing in Iran. Due to the possibility of irrigating this plant with saline water, it can play an important role in providing the required feed to livestock in areas with saline soil and water by producing significant grains with high protein content. The aim of this study was to investigate effect of different levels of kochia seed in high concentrate diets on rumen fermentation.Materials and Methods: Dietary treatments included control diet (no kochia seed) and three diets levels containing 10, 20 and 30 % of ration DM kochia seed. In all treatments, soybean meal and wheat bran in the diet were substituted with kochia seed. Gas production and dual-flow continuous culture system were used in this study. In the gas production test, treatments arranged as complete randomized design. The amount of gas produced in the samples was recorded at different hours after incubation and the parameters of gas production, organic matter digestibility and metabolic energy were calculated. In the second experiment, eight dual-flow continuous culture fermenters (1320 ml) were used in two periods (7 days adaptation, 3 days sampling). In each period, fermenters were randomly assigned to treatments. Temperature (38.5°C) and liquid and (10%/h) solid (5%/h) dilution rates were kept constant in the fermenters. Anaerobic conditions were maintained by the infusion of N2 at a rate of 40ml/min. Treatments were randomly assigned to fermenters. Fermenters were fed daily with 97 g dry matter. During sampling days, collection vessels were maintained at 4ºC to impede microbial action. Solid and liquid effluents were mixed and homogenized for 1 min, and a 500ml sample was removed via aspiration. Upon completion of each period, effluent from the 3 days of sampling was composited and mixed within fermenter and homogenized for 1 min. Subsamples were taken for total N, ammonia-N, and VFA analyses. Data were analyzed using the GLM procedure of SAS. Fermenter and period were considered random effects. Comparisons between treatments were completed with Tukey’s test. Effects were considered significant at P<0.05.Results and Discussion: Inclusion of kochia seed in the diet increased gas production potential and amount of produced gas compared to the control diet. Increasing levels of kochia seed in the diet linearly increased metabolizable energy, organic matter digestibility and short chain fatty acid production. Low lignin content and high hemicellulose digestibility could be the main reasons behind higher metabolizable energy and organic matter digestibility observed in kochia containing diets. The observed increase in gas production potential as well as the volume of produced gas in kochia seed containing diets also supports that this feedstuff does not contain antinutritional factors with antimicrobial properties or the amount of these compounds in the grain is not significant. In the dual flow continuous culture study, dry matter digestibility linearly increased with increasing levels of kochia seed in the diet. Organic matter digestibility tended to increase using kochia seed in the diet (P =0.08). An increase in protein digestibility observed in treatments containing 20 and 30 % kochia seed compared to other treatments. Total VFA concentration increased linearly in diets containing kochia seed (P = 0.01). This finding could be the result of higher organic matter digestibility in kochia seed containing diets. Also, it has been suggested that higher rumen fiber digestibility or partial replacement of starch with a digestible cell wall can increase the total VFA concentration by increasing the population of fiber-degrading bacteria, a mechanism that is especially important in high-concentrate diets. Average ammonia nitrogen concentration, the concentration before feeding and 2 hours after feeding decreased in kochia containing diets compared to control diet. Despite the increase in crude protein digestibility in diets containing 20 and 30% kochia seed, the average ammonia nitrogen concentration in these treatments was lower compared to the control treatment. This finding can be the result of higher use of ammonia nitrogen in these treatments. The higher digestibility of dry matter and the tendency to increase the digestibility of organic matter by increasing level of kochia seed in the diet could support this idea.Conclusion: The results of this study showed that using kochia seed in the diet up to 30% of ration dry matter could support optimal rumen fermentation. Due to the low water requirement and the ability of kochia plant to grow in saline soils on the one hand and the desirable energy and protein content of kochia seeds on the other hand, this grain can be used as a suitable option to meet part of the feed needed for ruminants in saline areas. Limited information is available and more in vivo research is needed in this area.